Additions to Diatrypaceae (Xylariales): Novel Taxa and New Host Associations - Naghmeh Afshari; Omid Karimi; Antonio R. Gomes de Farias; Nakarin Suwannarach; Chitrabhanu S. Bhunjun; Xiang-Yu Zeng; Saisamorn Lumyong (Journal of Fungi, 2023)
Diatrypaceae members have a broad distribution and are commonly found on decaying wood. Despite taxonomic and morphological challenges within this group, there has been a growing interest in Diatrypaceae in recent years. The dead branches of several plant hosts with fungal fruiting bodies were collected from Doi Tung National Park, Chiang Rai, and the Narathiwat Provinces in Thailand. Their morphological characteristics, coupled with a molecular phylogeny of combined ITS and tub2 sequence data, were used to introduce two novel Allodiatrype species (A. dalbergiae and A. eleiodoxae) and one new Melanostictus species (M. chiangraiensis). Moreover, four new host records, Diatrypella heveae, D. major, Melanostictus thailandicus, and Paraeutypella citricola on Microcos paniculata, Nayariophyton zizyphifolium, Dalbergia cultrata, and M. paniculata, respectively, as well as a new geographical record of D. major are reported. This research provides detailed descriptions of macro- and microcharacteristics, coupled with a phylogenetic tree for the newly introduced species and host records. The morphological features of Allodiatrype and Melanostictus are listed in the synoptic table.